The Inflammasome in Times of COVID-19 - de Rivero Vaccari, Juan Carlos; Dietrich, W. Dalton; Keane, Robert W.; de Rivero Vaccari, Juan Pablo (Frontiers in Immunology, 2020)
Coronaviruses (CoVs) are members of the genus Betacoronavirus and the Coronaviridiae family responsible for infections such as severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS) and more recently, coronavirus disease-2019 (COVID-19). CoV infections present mainly as respiratory infections that lead to acute respiratory distress syndrome (ARDS). However, CoVs, such as COVID-19, also present as a hyperactivation of the inflammatory response that results in increased production of inflammatory cytokines such as interleukin (IL)-1 and its downstream molecule IL-6. The inflammasome is a multiprotein complex involved in the activation of caspase-1 that leads to the activation of IL-1 in a variety of diseases and infections such as CoV infection and in different tissues such as lungs, brain, intestines and kidneys, all of which have been shown to be affected in COVID-19 patients. Here we review the literature regarding the mechanism of inflammasome activation by CoV infection, the role of the inflammasome in ARDS, ventilator-induced lung injury (VILI) and Disseminated Intravascular Coagulation (DIC) as well as the potential mechanism by which the inflammasome may contribute to the damaging effects of inflammation in the cardiac, renal, digestive and nervous systems in COVID-19 patients.